A biomimetic and pH-sensitive polymeric micelle as carrier for paclitaxel delivery. Issue 1 (16th August 2017) - Ma, Boxuan; Zhuang, Weihua; Liu, Gongyan; Wang, Yunbing
Abstract: As nano-scale drug delivery systems, smart micelles that are sensitive to specific biological environment and allowed for target site-triggered drug release by reversible stabilization of micelle structure are attractive. In this work, a biocompatible and pH-sensitive copolymer is synthesized through bridging poly (2-methacryloyloxyethyl phosphorylcholine) (PMPC) block and poly (D, L -lactide) (PLA) block by a benzoyl imine linkage ( Blink ). Biomimetic micelles with excellent biocompatibility based on such PLA- Blink -PMPC copolymer are prepared as carriers for paclitaxel (PTX) delivery. Due to the rapid breakage of the benzoyl imine linkage under acidic condition, the micelle structure is disrupted with accelerated PTX release. Such pH-sensitive triggered drug release behavior in synchronization with acidic conditions at tumor site is helpful for improving the utilization of drug and facilitating antitumor efficacy. These micelles can be used as promising drug delivery systems due to their biocompatible and smart properties.